Driven Understanding and Harnessing the Genetic Gifts Shared by Entrepreneurs, Navy SEALs, Pro Athletes, and Maybe You - Douglas Brackmann PhD and Randy Kelley ([Nevada, US] Lioncrest Publishing, 2017)
Some people are born with a drive often seen in entrepreneurs, pro-athletes, inventors, adventurers, and Navy SEALs. It's in their DNA - research has shown that certain genes can manifest resilient and highly focused people who can also be impulsive and easily distracted.
Keywords: Entrepreneurs